Anatomical and visual outcome of intravitreal bevacizumab (Avastin) in patients with diabetic macular edema - Vyas, Shyam; Thapa, Raba; Bajimaya, Sanyam; Pradhan, Eli; Paudyal, Govinda (Nepalese Journal of Ophthalmology, 2016)
Background: Intravitreal bevacizumab has been shown to be an effective treatment of diabetic macular edema. Objective: To assess the anatomical and visual outcome of intravitrealbevacizumab (Avastin) in patients of diabetic macular edema. Materials and methods: 52 eyes of 33 patients with diabetic retinopathy with CSME were included in this study. Detailed ophthalmic examination, including best-corrected visual acuity(BCVA), stereoscopic biomicroscopy, and retinal thickness measurement by Optical coherence tomography (OCT), was done at baseline and at each follow- up visit. All patients were treated with 0.05 mL intravitreal injection containing 1.25 mg of bevacizumab and repeat injection was given in cases of recurrent/persistent subretinal or intraretinal fluid shown by OCT and deterioration of BCVA. Results: All patients completed 6 months of follow-up with mean number of 2.78 intravitreal injections per eye.The mean BCVA at baseline was 0.80 log MAR, with significant changes 0.68 (p=0.012), 0.63 (p=<0.001) and 0.60 log MAR (p=<0.001) at 6 weeks, 3 months, and 6 months respectively. Final BCVA analysis demonstrated that 25 eyes (48.07%) remained stable and 22 (42.30%) improved ≥2 lines on BCVA. The mean central retinal thickness was 449.03 μm at baseline and it decreased significantly to 410.09 (p<0.001),345.76(p<0.001), 344.55(p<0.001) and 326.51(p<0.001) at 1st day, 6 weeks, 3 months and 6 months post injection, respectively. Mean macular volume changed significantly from baseline of 10.77 μm to 10.33μm (p<0.001) 8.97 (p<0.001), 8.82 (p<0.001), 8.95 (p<0.001) at 1st day, 6 weeks, 3 months and 6 months post injection respectively. Conclusion: Intravitreal bevacizumab injection resulted in significant improvement in BCVA, central retinal thickness and total macular volume in patients with diabetic retinopathy with CSME, and this beneficial effect is maximum at 6 weeks. Also, slight reduction in these parameters at 3 month follow up suggests that visual improvement and stable macular thickness can be maintained longer with injection frequency of probably 6-12 weeks. Nepal J Ophthalmol 2016; 8(15): 54-61